Modeling of thermal behavior in phase change interconnects - Eng, Wee Hock (2010)
A reconfigurable via with a phase change material, Ge2Sb2Te5 material is an interesting prospect to replace the current reconfigurable device technology. Its scalability, thermal stability and ability to achieve high-performance reconfigurable logic application without significantly sacrificing logic gate density or power deserves to more research attention. Similar to phase change memories, a phase change interconnect uses the high resistance ratio between the ON/ OFF state by switching between a polycrystalline and amorphous Ge2Sb2Te5 states respectively activated by joule heating. Therefore knowing the heating and the temperature profile of the Ge2Sb2Te5 is critical for optimizing device scalability, programming rates, power requirements, and minimizing thermal stresses. This report proposes an efficient thermal model by simulating a finite element partial differential equation using MATLAB built in PDETOOL application. It solves the equation and outputs the graphical time- and position-dependent temperature distributions contours with the relative heat scales. After that, these data are exported to be post processed with a user input program to analyze the heat flux and flow along the interconnect. Thus using this model to further explore the thermal profile between two patented phase change interconnect structures.